GENDER JUSTICE IN THE SHARING OF INHERITANCE AND IMPLEMENTATION IN INDONESIA - Hisam Ahyani; Haris Maiza Putra; Muharir Muharir; Encep Taufik Rahman; Mustofa Mustofa (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2022)
Fairness in inheritance distribution between men and women in Indonesia is still an exciting topic to discuss. It is proven that classical Islamic thought says that men's and women's portions in inheritance distribution are final, as stated in the Qur'an Surat an-Nisa verse 11. However, contemporary Islamic thought sees it as a rule that needs to be contextualized to current situations. This progressive thinking about inheritance distribution was pioneered by gender activists who saw that Fiqh Mawaris has a gender bias and discrimination. Therefore, the application of the